Detection of Pancreatic Cancer via Specific Metabolite Markers: A Metabolomics Approach - Mohammad Javad Roustaye Gourabi; Mehrangiz Ghafari; Anita Nikoo; Yalda Yarahmadi Saki; Bita Khanbabaei; Masoumeh Khanizadeh; Masoud Kargar; Ali Hashemi; Javad Yasbolaghi Sharahi (Health Science Reports, 2026)
ABSTRACT Background and Aims Pancreatic ductal adenocarcinoma (PDAC) remains one of the most lethal malignancies worldwide because most patients are diagnosed at advanced stages when curative treatment is no longer feasible. Metabolomics has emerged as a promising strategy for identifying biochemical alterations associated with early tumor development and may improve the early detection of PDAC. This review critically evaluates the role of metabolomics in PDAC diagnosis, focusing on metabolite biomarkers, nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry‐based platforms, and machine learning assisted approaches. Methods A narrative review of the current literature was conducted to assess the diagnostic potential, analytical methodologies, and translational challenges of metabolomics in PDAC. Evidence related to metabolite biomarkers, analytical platforms, artificial intelligence applications, and clinical implementation was critically examined. Results PDAC is characterized by significant alterations in glycolysis, amino acid metabolism, lipid metabolism, and microbiome derived metabolites. Several metabolite panels have demonstrated promising diagnostic performance, particularly when combined with CA19‐9. Advanced analytical platforms, including NMR spectroscopy, liquid chromatography mass spectrometry, and gas chromatography mass spectrometry, have enabled detailed characterization of metabolic signatures and improved discrimination between PDAC and benign pancreatic diseases such as chronic pancreatitis. However, clinical translation remains limited by methodological heterogeneity, biological variability, lack of standardized analytical workflows, interlaboratory reproducibility concerns, and insufficient prospective multicenter validation. Although machine learning has enhanced biomarker discovery and pattern recognition, challenges related to overfitting, interpretability, and external validation remain unresolved. Conclusion Metabolomics is unlikely to replace existing diagnostic modalities in the near future but may substantially improve diagnostic accuracy when integrated with established biomarkers, imaging techniques, and molecular diagnostics. Future progress will depend on standardized protocols, large prospective validation studies, and clearly defined regulatory pathways. With these advances, metabolomics may become an important component of precision diagnostic strategies for PDAC.